Preliminary validation of developmental weight suppression in youth with transdiagnostic eating disorders - Simar Singh; Erin E. Reilly; Catherine R. Drury; Alan Duffy; Philip S. Mehler; Erin C. Accurso; Kianna Zucker; Naomi Lynch; Daniel Le Grange; Renee D. Rienecke; Sasha Gorrell (Journal of Eating Disorders)
Abstract Background Weight suppression (WS), traditionally defined as the difference between highest past and current weights at adult height, is a correlate and predictor of eating disorder (ED) psychopathology. However, for growing adolescents, it may be more appropriate to use a developmentally-adjusted calculation of WS. This study compared how developmental WS, calculated using zBMIs, compared with traditional WS, calculated using weights, as correlate of ED psychopathology in treatment-seeking adolescents with transdiagnostic EDs. Methods Adolescents with EDs (N = 93) completed the Eating Disorder Examination Questionnaire (EDE-Q) at presentation to outpatient care. Weight histories were extracted from medical records. Regressions examined the association between each measure of WS and EDE-Q scores, adjusting for ED diagnosis. Dominance analyses with bootstrapping assessed whether developmental WS outperformed traditional WS. Results Developmental WS negatively associated with EDE-Q Shape (sr 2   = 0.05, p =.020) and Weight Concern (sr 2   = 0.05, p =.021). In contrast, traditional WS did not associate with any EDE-Q scores. Although dominance weights were larger for developmental WS compared to traditional WS, bootstrap sampling revealed no significant differences in magnitudes. Conclusions Results preliminarily support developmental WS as a correlate of body image concerns in youth with EDs, though replication is needed.